1999
DOI: 10.1001/archneur.56.8.991
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Progression of Dementia in a Community Population Aged 75 Years and Older

Abstract: The use of diuretics may protect against dementia in elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
11

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(133 citation statements)
references
References 42 publications
4
118
0
11
Order By: Relevance
“…159 Moreover the results of the non-randomised, observational, Kungsholmen Project showed that antihypertensive treatment and particularly, but not only, diuretics may protect against dementia in the elderly. 160 Furthermore, the HOPE study also showed that long-term blood pressure control by diuretics or ACE inhibitors may reverse cognitive impairment associated with pre-existing hypertension. 161 A deleterious effect of calcium channel blockers on cognitive function has been suspected in a cross-sectional study 162 and in a 5-year prospective study.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…159 Moreover the results of the non-randomised, observational, Kungsholmen Project showed that antihypertensive treatment and particularly, but not only, diuretics may protect against dementia in the elderly. 160 Furthermore, the HOPE study also showed that long-term blood pressure control by diuretics or ACE inhibitors may reverse cognitive impairment associated with pre-existing hypertension. 161 A deleterious effect of calcium channel blockers on cognitive function has been suspected in a cross-sectional study 162 and in a 5-year prospective study.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Active lowering of BP should prevent or reduce cognitive impairment, although not all antihypertensive agents seem to be equally effective in this regard. [4][5][6][7][8] Growing evidence has suggested that the reninangiotensin system (RAS) in the central nervous system participates in the processing of sensory information, learning and memory. 9,10 Brain angiotensin II (Ang II) and its fragments Ang IV and Ang III have been shown to influence performance in learning and memory paradigms directly or by modulating the activity of other neurotransmitters, like acetylcholine, catecholamines, serotonin and other peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Na mesma direção, um estudo prospectivo, participante do Longitudinal Population Study of 70-year-olds in Goteborg, Sweden, avaliou 382 indivĂ­duos de 70 a 85 anos, verificou a associação dos nĂ­veis pressĂłricos sistĂłlicos e diastĂłlicos com o aparecimento de quadro demencial (Skoog et al, 1996). Diversos estudos clĂ­nicos tĂȘm demonstrado que indivĂ­duos com HAS apresentam pior performance em testes neuropsicolĂłgicos que avaliam funçÔes como memĂłria, atenção, orientação e funçÔes executivas (Guo et al, 1999). IndivĂ­duos hipertensos apresentam pior performance em testes neuropsicolĂłgicos que avaliam funçÔes tais como o Mini Exame do Estado Mental (MEEM) (Bertolucci et al, 1994), Modulo Cognitivo do Cambridge Examination for the Elderly (CAMCOG), Digit Span e Digit Symbol (Hertzog et al, 1978;Guo et al, 1997;Heckbert et al, 1997;Guo et al, 1999;Havlik et al, 2002).…”
Section: Introductionunclassified